Novel target and cofactor repertoire for the transcriptional regulator JTY_0672 from Mycobacterium bovis BCG - Wang, Hui; Li, Xiaotian; Wang, Shuxian; Fang, Ren; Xing, Jiayin; Wu, Ruiying; Zhang, Chunhui; Li, Zhaoli; Song, Ningning (Frontiers in Microbiology, 2025)
Mycobacterium tuberculosis (Mtb) is the pathogenic agent of tuberculosis (TB). Intracellular survival plays a central role in the pathogenesis of Mtb in a manner that is dependent on an array of transcriptional regulators for Mtb. However, the functionality of JTY_0672, a member of the TetR family of transcriptional regulators, remains unknown. In this study, EMSA, BIL, ChlP-PCR and animal models were used to investigate the regulation function of this protein. We found that the transcriptional regulator JTY_0672 is a broad-spectrum transcriptional regulatory protein and can directly regulate JTY_3148, both in vitro and in vivo. Cofactors containing VB1, VB3, VB6, VC, His, Cys, Asp, Glu, Fe3+, Pb2+, Cu2+, and Li+ were found to inhibit binding between JTY_0672 and the promoter of JTY_3148. JTY_0672 enhanced TAG production and increased Isoniazid (INH) resistance. Besides, this protein either promoted recalcitrance to the host immune response and induced pathological injury and inflammation. In summary, this research identified new targets and cofactors of JTY_0672 and deciphered the physiological functionality of JTY_0672. Our findings will provide an important theoretical basis for understanding the Mtb transcriptional regulatory mechanism.